Diagnosis Sindrom Brugada - Edward Faisal (Jurnal Kardiologi Indonesia, 2014)
Brugada syndrome is an inherited autosomal dominant disease that cause sudden death, which related with mutation of SCN5A gene, ? subunit of sodium channel. The risk Brugada syndrome in male is 8 times more than females. The average age is 40 years old, which can happen between age 1 to 77 years old. The Incidence is 5 to 66 per 10.000 people. The golden diagnostic tools is ECG, an abnormality QRS-T found in lead V1-V3. I report a case of Brugada syndrome with neither sign nor symptoms. The disease coincidental in routine medical examination.